Bis(benzyltriethylammonium) hexachloridostannate(IV) - Najafi, E.; Amini, M.M.; Ng, S.W. (International Union of Crystallography, 2010)
The reaction between benzyltriethylammonium chloride and dimethyltin dichloride yields the title salt, [(C(6)H(5)CH(2))(C(2)H(5))(3)N](2)[SnCl(6)]. The Sn(IV) atom, located on a center of inversion, exists in an octahedral coordination environment. The cation links with the anion via weak C-H center dot center dot center dot Cl hydrogen bonding.